Deformable registration with intensity correction for CESM monitoring response to Neoadjuvant Chemotherapy. (1st May 2023) - Jailin, Clément; Milioni De Carvalho, Pablo; Mohamed, Sara; Vancamberg, Laurence; Amr Farouk Ibrahim, Moustafa; Gomaa, Mohammed Mohammed; Kamal, Rasha Mohammed; Muller, Serge
Abstract: This paper proposes a robust longitudinal registration method for Contrast Enhanced Spectral Mammography in monitoring neoadjuvant chemotherapy. Because breast texture intensity changes with the treatment, a non-rigid registration procedure with local intensity compensations is developed. The approach allows registering the low energy images of the exams acquired before and after the chemotherapy. The measured motion is then applied to the corresponding recombined images. The difference of registered images, called residual, makes vanishing the breast texture that did not changed between the two exams. Consequently, this registered residual allows identifying local density and iodine changes, especially in the lesion area. The method is validated with a synthetic NAC case where ground truths are available. Then the procedure is applied to 51 patients with 208 CESM image pairs acquired before and after the chemotherapy treatment. The proposed registration converged in all 208 cases. The intensity-compensated registration approach is evaluated with different mathematical metrics and through the repositioning of clinical landmarks (RMSE: 5.9 mm) and outperforms state-of-the-art registration techniques.